2013
DOI: 10.1080/10810730.2012.757398
|View full text |Cite
|
Sign up to set email alerts
|

Doctor Talk: Physicians' Use of Clear Verbal Communication

Abstract: Low health literacy negatively affects processes and outcomes of care. Physicians do not routinely use communication techniques recommended for use with low health literate patients. This study was conducted to compare the self-reported and actual use of clear verbal communication among medical residents and to identify characteristics associated with clear communication. Residents self-assessed their communication behaviors and then completed a low health literacy standardized patient encounter. Answers on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
67
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 22 publications
6
67
1
Order By: Relevance
“…A range of teaching approaches have been used, including video tape review, small group discussions, and standardized patients. 47,[51][52][53][54] Trainees and providers attending workshops on health literacy-informed strategies report improved confidence in their abilities to assess and counsel patients. 55,56 Provider participation in health literacy skillbuilding workshops improves provider skills and has a positive impact on patients, including greater patient confidence in medication management 57 and ability to lose weight, 58 increased preventive screening, 59 and decreased healthcare utilization.…”
Section: Teaching Health Literacy Skills To Physiciansmentioning
confidence: 99%
“…A range of teaching approaches have been used, including video tape review, small group discussions, and standardized patients. 47,[51][52][53][54] Trainees and providers attending workshops on health literacy-informed strategies report improved confidence in their abilities to assess and counsel patients. 55,56 Provider participation in health literacy skillbuilding workshops improves provider skills and has a positive impact on patients, including greater patient confidence in medication management 57 and ability to lose weight, 58 increased preventive screening, 59 and decreased healthcare utilization.…”
Section: Teaching Health Literacy Skills To Physiciansmentioning
confidence: 99%
“…Studies have identified low rates of formal training in health literate knowledge or communication skills for medical students and an unclear extent of training in this area for other health profession students. [11][12][13][14] Additionally, inconsistent implementation of health literacy practices across disciplines has been identified. 15 Often pharmacist competency development or training is designed as continuing education programming.…”
Section: Innovations In Pharmacymentioning
confidence: 99%
“…[2][3][4][5] However, no large-scale assessments have been conducted to measure the health literacy burden of the health care environment. In contrast, much is known about patients' health literacy skills.…”
Section: The Scope Of the Problemmentioning
confidence: 99%
“…6,8 Despite its prevalence, physicians and nurses routinely overestimate the literacy skills of their patients. 4,[9][10][11] For example, although pediatric gastroenterologists at the University of California and Rady Children's Hospital estimated that 47% of their IBD patients had adequate health literacy, only 11% of patients demonstrated objective evidence of such. 12 This striking disconnect should prompt reflection and examination of previously held beliefs and practices.…”
Section: The Scope Of the Problemmentioning
confidence: 99%